2014
DOI: 10.4161/viru.29002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of virulence and resistance profiles ofSalmonellaEnteritidis isolates from poultry meat and foodborne outbreaks in northern Jordan

Abstract: This study was conducted to isolate Salmonella Enteritidis from poultry samples and compare their virulence and antibiotic resistance profiles to S. Enteritidis isolated from outbreaks in northern Jordan. Two hundred presumptive isolates were obtained from 302 raw poultry samples and were subjected to further analysis and confirmation. A phylogenic tree based on 16S rRNA sequencing was constructed and selected isolates representing each cluster were further studied for their virulence in normal adult Swiss whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Enterobacter cloacae and K. oxytoca are not considered significant causes of foodborne diseases with few reporting on their occurrence in foods (Feglo & Sakyi, 2012;Jarvis et al, 2018;Nyenje, Odjadjare, et al, 2012; (Jaradat et al, 2014). In our study, Cronobacter spp.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Enterobacter cloacae and K. oxytoca are not considered significant causes of foodborne diseases with few reporting on their occurrence in foods (Feglo & Sakyi, 2012;Jarvis et al, 2018;Nyenje, Odjadjare, et al, 2012; (Jaradat et al, 2014). In our study, Cronobacter spp.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, in the elderly or immunocompromised, infections due to Cronobacter spp. exposure from foods such as dried meats, legumes, nuts, floured spices have been documented (Jaradat et al, ). In our study, Cronobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in south-east Asian countries, such as Philippines showed a prevalence rate of 4.9%NTS from poultry (16), and Vietnam showed 45.6% (19). Jordan showed the highest prevalence of 66% (20), farm prevalence of Nigeria was 43.6% (21), Japan was 54% (13), Egypt was 14.3% (22), Iraq was 10.39% (23) and the United States of America showed 12.4% (24). The occurrence of Salmonella serovars differed among different states of our country where the investigation was done.…”
Section: Discussionmentioning
confidence: 99%
“…High incidence of resistance against streptomycin, tetracycline, trimethoprim, trimethoprim sulfomethoxazole, nalidixic acid have also been declared from Spain [14] , Vietnam [22] , Brazil [15] , Pakistan [16] , Turkey [17] , China [18] , Albania [19] , Ireland [23] , Jordan [24] . Antimicrobial resistance poses a threat to human health and the food animal reservoir is an important source.…”
Section: Discussionmentioning
confidence: 99%